Strategic Financial Planning and Business Growth Among Small and Medium Enterprises in North West Nigeria - Vincent Olawale Bamidele; Abdulsalam Dauda (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Financial planning is fundamental to the survival and growth of firms, yet in developing regions such as North West Nigeria, its application among small and medium enterprises (SMEs) is often limited due to resource constraints and pervasive uncertainty. Despite SMEs accounting for over half of national employment, the region experiences high SME mortality rates, partly attributed to weak financial management systems.Purpose: This study investigates the impact of strategic financial planning practices on the business growth of SMEs across the seven states of North West Nigeria, providing region-specific empirical evidence.Design/methodology/approach: Anchored on Agency Theory and Pecking Order Theory, the study employs a quantitative correlational design. Primary data were collected from 332 SME owners/managers selected through multistage random sampling. Analytical methods included descriptive statistics, Pearson correlation, Ordinary Least Squares (OLS) regression, and Generalized Linear Modeling (GLM) to ensure robustness.Findings/Result: The results reveal a significant and positive relationship between financial planning and SME business growth (β = 1.846; p < 0.001). SMEs that implemented structured budgeting, goal setting, cash flow forecasting, and capital expenditure planning achieved higher growth in assets, sales, and employment. Model diagnostics confirmed the robustness of these findings (Adjusted R² = 0.674; Deviance/df = 1.03).Conclusion: Strategic financial planning acts as a catalyst for SME growth by enabling efficient forecasting, allocation, and control of resources, even in uncertain environments. The study recommends institutionalizing periodic financial plans, adopting digital forecasting tools, and implementing targeted training programs for SME owners.Originality/value (State of the art): This research provides novel, region-specific empirical evidence on the role of financial planning in SME growth within North West Nigeria, addressing a gap in the literature and reinforcing the enduring importance of financial planning in resource-constrained settings. Keywords:   financial planning, budgeting, forecasting, business growth, small and medium enterprises, North West Nigeria